Needs assessment survey of healthcare providers’ perceptions and practices regarding delirium prevention at a university medical center - Alghamdi, Bushra; Koroukian, Siran M.; Kresevic, Denise; Drummond, Colin K. (Frontiers in Aging, 2022)
Background Despite the high prevalence and serious implications of delirium, identification, tracking, and documentation of the condition remain a challenge for the health care team, impeding management of patients. This survey is the first phase of a qualitative study to support building a conversational agent-based tool for screening and managing delirium-prone patients. Our objective is to assess healthcare providers’ perceptions of delirium management, focusing on patient assessment, therapeutic interventions, and subsequent communication and documentation. An electronic web-based survey was distributed to healthcare providers identified as caring for inpatient acutely ill older adults admitted for medical and orthopedic surgery needs. Respondent contact information was removed to preserve anonymity. We conducted this survey in a 1000 bed university-affiliated teaching hospital in an urban setting. The analysis of survey responses provided insight into providers' current experiences with delirium assessment tools including computerized documentation, as well as their perceptions and attitudes toward delirium prevention. A majority of providers affirmed that current delirium protocols are helpful; however, existing screening instruments and methods for documentation are cumbersome, resulting in incomplete or limited documentation of episodes. These barriers lead to an understatement of evidence available for continuous improvement of the patient management process.